Ab Initio Study of the Adsorption of Small Molecules on Metal-Organic Frameworks with Oxo-centered Trimetallic Building Units: The Role of the Undercoordinated Metal Ion - Mavrandonakis, Andreas; Vogiatzis, Konstantinos D.; Boese, A. Daniel; Fink, Karin; Heine, Thomas; Klopper, Wirn (Inorganic Chemistry, 2015)
The interactions of H2, CO, CO2, and H2O with the undercoordinated metal centers of the trimetallic oxo-centered M3III(μ3-O)(X) (COO)6 moiety are studied by means of wave function and density functional theory. This trimetallic oxo-centered cluster is a common building unit in several metal-organic frameworks (MOFs) such as MIL-100, MIL-101, and MIL-127 (also referred to as soc-MOF). A combinatorial computational screening is performed for a large variety of trimetallic oxo-centered units M3IIIO (M = Al3+, Sc3+, V3+, Cr3+, Fe3+, Ga3+, Rh3+, In3+, Ir3+) interacting with H2O, H2, CO, and CO2. The screening addresses interaction energies, adsorption enthalpies, and vibrational properties. The results show that the Rh and Ir analogues are very promising materials for gas storage and separations.
CRIS-Team Scopus Importer:2023-03-20